Indigenous Parents Navigating School Choice in Constrained Landscapes. Issue 2 (3rd April 2017) - Anthony-Stevens, Vanessa
ABSTRACT: Educational reform policies in the United States promote school choice as a central tool to empower low-income and minoritized families in order to close the achievement gap. However, research on school choice rarely reflects the voice of minoritized families and offers little evidence that choice significantly addresses inequities in educational outcomes. This article analyzes the perspectives of Indigenous parents as they navigate school choice options with their children in the southwestern U.S. Through the conceptual lens of enduring struggle and educational survivance, ethnographic data offers insight into factors significant for three families as they select schools from a highly constrained landscape. Deeper analysis of why Indigenous families reject and select schools reveals an educational landscape fraught with persisting inequities, in spite of choice. The continued silencing of issues relevant to Indigenous education, such as the impacts of colonization, tribal sovereignty, and rights to culturally responsive education marginalize Indigenous voices from the school choice debate. This study adds Indigenous voices to the school choice debate, and contributes new dimensions to parent choice behaviors. Implications support scholarly claims that current school choice policy masks the entrenched operations of race, class and deficit discourse which perpetuate unfavorable school outcomes for Indigenous youth.